Consumers‟ Willingness to Pay for Malaysian Organic Food Product - Ahmed, Siddique; Siwar, Chamhuri; Ferdous Alam, A.S.A.; Abdul Talib, Basri; Chamhuri, Norshamliza; Diana Mohd Idris, Nor (International Journal of Psychosocial Rehabilitation, 2020)
In the global food market, there exists a growing need for organic food, and in this context, country of origin is very crucial for consumers for organic food choice. The purpose of this paper is to explore the perception of consumers towards different country-of-origin organic foods available in the Malaysian market and their willingness to pay for these organic foods. Based on survey data of 330 respondents, ‘principal component analyses’ and’multiple correspondence analysis’ techniques were applied for analyzing the data. The study finds that consumers’ perceptions towards different country-of-origin organic logos are not homogenous, and they consider OECD organic products, East Asian organic products, and Malaysian organic products as three distinct categories. But these distinctions do not necessarily translate into their willingness to pay. The study identifies a basis for segmenting organic food markets with respect to country-of-origin that can create new thinking among the different actors of the global organic food market chain and domestic government and non-government policymakers. The study prompted a new dimension in organic food research by combining it with the country-of-origin aspect.